IN VITRO TESTING OF A POLYLACTIC POLYMER SYNTHESIZED FROM WHEY - DREANCĂ, Alexandra; POPESCU, Radu A.; NEAGU, Amalia; ENACRACHI, George; CIMPOEȘ, Iulia; FIȚ, Nicodim Iosif; MOLDOVAN, Marioara; SILAGHI DUMITRESCU, Laura; JURJ, Anca Maria; BERINDAN-NEAGOE, Ioana; MARCUS, Ioan (Studia Universitatis Babeș-Bolyai Chemia, 2018)
The main purpose of this research is in vitro biocompatibility testing of a polylactic acid polymer (PLA) synthesized by the condensation of lactic acid separated from whey (Zonar). The experimental PLA obtained was characterized by: Scanning Electron Microscopy which pointed a homogeneous microstructure of the polymer without a separation phase and differential scanning calorimetry (DSC) analysis which indicated a melting point of 1740C of the biomaterial. The cytotoxicity test for experimentally obtained polymer was performed according to ISO 10 993 -123. Six solutions of different concentrations were prepared (30 mg/ml, 20 mg/ml, 10 mg/ml, 5 mg/ml, 2.5 mg/ml and 1.25 mg/ml) and were tested on a fibroblast culture at 48 hours using MTT cell viability and proliferation assay. At 48h the obtained polylactic polymer showed good compatibility with an IC 50 of 64.82 mg/ml. The results showed that the cytotoxicity level can be influenced by the period of time in which the extract acts on the cell culture.